Prospects for Islamic Economic Development in the Digital Era - Alip Toto Handoko; M. Abdul Aziz; Muhamad Ulul Fahmi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The development of the digital era has compelled all sectors, including Islamic banking, to undergo digitalization. Coupled with the advent of Digital Financial Innovation (DFI), Islamic banks must participate in this transformation to avoid being left behind. Therefore, it is crucial to study the prospects for the future development of the Islamic economy by examining the opportunities and challenges faced by Islamic banks to survive and continue to thrive in the current era of digitalization. The research method in this article is descriptive qualitative. The analysis results indicate that: Islamic Banking as a New Business Model Organizer, Islamic Banking is one of the organizers of a new business model known as